2019
DOI: 10.1002/acm2.12733
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the RayStation Monte Carlo dose calculation algorithm using realistic animal tissue phantoms

Abstract: Purpose Our purposes are to compare the accuracy of RaySearch's analytical pencil beam (APB) and Monte Carlo (MC) algorithms for clinical proton therapy and to present clinical validation data using a novel animal tissue lung phantom. Methods We constructed a realistic lung phantom composed of a rack of lamb resting on a stack of rectangular natural cork slabs simulating lung tissue. The tumor was simulated using 70% lean ground lamb meat inserted in a spherical hole with diameter 40 ± 5 mm carved into the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…We interpret the systematic improved passing rate for a uniform scaling of the HU‐to‐MD curve as mainly being caused by the difference in interpreted and the real stopping power of cork. This assumption is supported by the results in the previous study where only animal tissues were used together with the original HU‐to‐MD curve . As mentioned earlier we recalculated all the beams with a modified HU‐to‐MD curve where the mass density was increased by 5% over the cork region only.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…We interpret the systematic improved passing rate for a uniform scaling of the HU‐to‐MD curve as mainly being caused by the difference in interpreted and the real stopping power of cork. This assumption is supported by the results in the previous study where only animal tissues were used together with the original HU‐to‐MD curve . As mentioned earlier we recalculated all the beams with a modified HU‐to‐MD curve where the mass density was increased by 5% over the cork region only.…”
Section: Resultssupporting
confidence: 56%
“…The 5% shift is within the uncertainty of 7% in the measured stopping power for cork, as detailed above. Because our work using animal neck phantoms and a water‐based breast phantom revealed that the HU‐to‐MD curve in the soft tissue, water and bone region is adequately accurate, we decided to leave that portion of the HU‐to‐MD curve unchanged …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proton pencil beam scanning (PBS) systems are increasingly being employed for radiation therapy due to greater control over homogeneity and conformality of the dose distribution without the use of patient‐specific compensators 1 . As clinics transitioned away from passive scattering proton therapy, studies showed that analytical algorithms were not adequate for beam modeling and dose calculation of PBS treatments 2–7 . Often, the analytical algorithm‐based treatment planning software (TPS) overestimated dose to the target, while underestimating dose to organs at risk 4 .…”
Section: Introductionmentioning
confidence: 99%